Miss Toronto acts back: observing and thinking in montage - Fitzsimmons Frey, Heather (My University, 2016)
Based on interviews with the DitchWitch Brigade, who created Miss Toronto Acts Back, this review discusses the group’s multimedia, semi-historical, stylistically diverse montage that playfully examined the story of the Miss Toronto Beauty Pageant, while questioning issues of beauty, gender performance, and spectator- performer relations.
Keywords: gender performance; beauty pageants; burlesque; montage; spectators